2013
DOI: 10.5575/geosoc.2013.0007
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Uppermost Alluvium in the Tokyo and Nakagawa Lowlands, Kanto Plain, central Japan: response to the "Yayoi regression"

Abstract: The age and depth of the Uppermost Alluvium in the coastal lowlands of Japan indicates that minor sea-level drop, termed the Yayoi regression , occurred at-ka; however, this Yayoi regression is not a eustatic phenomenon. Sedimentary facies analysis and radiocarbon dating in the Tokyo and Nakagawa Lowlands indicate that: () flood plain sediments of the Uppermost Alluvium are located at depths > m below the present sea level, and () the morphology of fluvial channel sediments of the Uppermost Alluvium changes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For example, minor sea level fluctuation is a typical phenomenon of short-term environmental change and caused by glacio-, hydro-, and sediment-isostastic movements through the middle to late Holocene. It was strongly related to paleoenvironmental changes in Japanese coastal areas (Umitsu, 1994;Tanabe and Ishihara, 2013;Matsubara, 2015). Generally speaking, high stand sea level of the post-glacial transgression (Jomon Transgression) around the Japanese archipelago was reached in the middle Holocene (around 6e8 ka) and after this, relative sea level generally fell, with minor fluctuations, as a result of hydro-isostatic uplift (Ota et al, 1990;Nakada et al, 1991;Umitsu, 1991;Yokoyama, 2002).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, minor sea level fluctuation is a typical phenomenon of short-term environmental change and caused by glacio-, hydro-, and sediment-isostastic movements through the middle to late Holocene. It was strongly related to paleoenvironmental changes in Japanese coastal areas (Umitsu, 1994;Tanabe and Ishihara, 2013;Matsubara, 2015). Generally speaking, high stand sea level of the post-glacial transgression (Jomon Transgression) around the Japanese archipelago was reached in the middle Holocene (around 6e8 ka) and after this, relative sea level generally fell, with minor fluctuations, as a result of hydro-isostatic uplift (Ota et al, 1990;Nakada et al, 1991;Umitsu, 1991;Yokoyama, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…Relative sea level curves A and B are for the region around Ise Bay ( Fig. 1A; calibrated after Umitsu (1992) using IntCal 13.14c) and around the Tokyo lowland (Tanabe and Ishihara, 2013), respectively. 3500 cal BP from the age model, Thalassiosira sp., an indicator of an outer bay environment (Kosugi, 1988), increased, suggesting that the inflow of seawater increased at that time.…”
Section: Stage III (Ca 4500e2650 Cal Bp)mentioning
confidence: 99%
See 1 more Smart Citation
“…BP is considered to result from the cessation of eustatic sea-level rise (Yokoyama et al, 2012, 2015) and generally recognized as a smooth multimillennial trend (Sato, 2008; Tanabe et al, 2003; Yokoyama et al, 1996), some coastal studies in Japan have shown that a relative sea-level fall of a few meters could have occurred over a span of several centuries to a millennium between 5000 and 2000 cal. BP (Kawase, 1998; Ohira and Umitsu, 1999; Ono, 2004; Ota et al, 1990 and references therein; Tanabe and Ishihara, 2013). In the innermost areas of the Tonegawa Lowland, Tanabe et al (2016) noted that a relative sea-level fall because of isostatic movements triggered by sediment loading might have occurred during 4000–3000 cal.…”
Section: Discussionmentioning
confidence: 99%